Οι αντιλήψεις των Ατόμων με Σοβαρά Προβλήματα Όρασης για τη Διαθέσιμη στο Περιβάλλον τους Κοινωνική Στήριξη - Χάλαζα Βασιλική; Αργυρόπουλος Βασίλειος (Education Sciences, 2013)
THe purpose of the present study was to investigate the perceptins of 20 indiviluals with visual impairments across their social support provided by family, friends and professionals. More specifically, it examined the participants’ descriptions and evaluations of the informational, instrumental, and emotional social support they had been receiving from their environments. Data were generated from one-to-one and face-to-face semistructured interviews. The findings of the study indicated the factors which had an impact on the participants’ perceptions and satisfaction regarding the framework and structures of the social support which was available in their environments.